2012
DOI: 10.1021/nl3018115
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned GaAs Nanowires on Graphite and Few-Layer Graphene: Generic Model and Epitaxial Growth

Abstract: By utilizing the reduced contact area of nanowires, we show that epitaxial growth of a broad range of semiconductors on graphene can in principle be achieved. A generic atomic model is presented which describes the epitaxial growth configurations applicable to all conventional semiconductor materials. The model is experimentally verified by demonstrating the growth of vertically aligned GaAs nanowires on graphite and few-layer graphene by the self-catalyzed vapor-liquid-solid technique using molecular beam epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
258
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(272 citation statements)
references
References 39 publications
9
258
2
3
Order By: Relevance
“…[32][33][34] Recent works on epitaxy of III-V nanowires on graphene also discussed the possible rotated in-plane epitaxial relationships or different nanowire growth directions presumably caused by lattice mismatch when covalent epitaxial links exist at the heterointerface. 35,36 Hence, it is strongly suggested that the observed domain-aligned heteroepitaxial relationship of ZnO/hBN should result from weakly bound vdW heterointerfaces.…”
Section: Epitaxy Of Zno Nanostructures On Hbn H Oh Et Almentioning
confidence: 99%
“…[32][33][34] Recent works on epitaxy of III-V nanowires on graphene also discussed the possible rotated in-plane epitaxial relationships or different nanowire growth directions presumably caused by lattice mismatch when covalent epitaxial links exist at the heterointerface. 35,36 Hence, it is strongly suggested that the observed domain-aligned heteroepitaxial relationship of ZnO/hBN should result from weakly bound vdW heterointerfaces.…”
Section: Epitaxy Of Zno Nanostructures On Hbn H Oh Et Almentioning
confidence: 99%
“…Inset (ii) of Figure 2c shows that the position of the (10) streak from CVD graphene layers was aligned indistinguishably with that of 112l À Á InAs Bragg spots, implying a possible in-plane, lattice-matching configuration of InAs crystals and graphene layers. 16,21 For longer growth times approaching 1 h and InAs nanorod lengths reaching 10 μm, sharp spots were clearly visible in the RHEED patterns (Figure 2b) thanks to the transmission mode of RHEED. 22 For all azimuthal rotation angles, the RHEED patterns from the InAs nanorods were the same, indicating that the nanorods were vertically well aligned along [0002] WZ and [111] ZB , but their in-plane orientations were random; these results were attributed to in-plane misorientations of grains in the CVD graphene layers.…”
Section: Catalystmentioning
confidence: 99%
“…For catalyst-free growth of InAs nanorods, we supplied As 4 to the substrates for 10 min before supplying In to prevent In droplet formation on the graphene layers, which resulted in quite different nucleation and crystal growth behavior from vapor-liquid-solid (VLS) growth. 14,16 After the preparation of InAs nanorods, InAs/In x Ga 1 − x As coaxial nanorod heterostructures were subsequently synthesized by heteroepitaxial growth of an In x Ga 1 − x As thin layer on InAs core nanorods. Deposition of In x Ga 1 − x As coaxial shell layers was performed at 380°C for 1 h by the addition of a gallium (Ga) molecular beam, resulting in an In x Ga 1 − x As layer coating over the entire InAs nanorod surface.…”
Section: Preparation Of Graphene Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 On the other hand, previous reports of growth on graphene deposited by chemical vapor deposition (CVD-graphene) have shown unsatisfactory growth controllability, with a lack of individual position control (i.e., a bundled growth), low growth selectivity, or poor vertical alignment. 16,17 Herein, we report a method to significantly enhance the growth controllability on CVD-graphene, enabling a wafer-scale preparation of individually position-controlled and vertically aligned 1D ZnO nanostructure arrays on arbitrary substrates including amorphous, metallic, or flexible substrates. The growth behaviors of semiconductor nanostructures on exfoliated and CVD-graphene are drastically different, which has led to different strategies for achieving position-controlled growth.…”
mentioning
confidence: 99%